Evaporation characteristics of dual component droplet of benzyl azides-hexadecane mixtures at elevated temperatures. (1st October 2015) - Han, Kai; Zhao, Changlu; Fu, Geng; Zhang, Fujun; Pang, Siping; Li, Yuchuan
Highlights: Evaporation characteristics of benzyl azides-hexadecane (BAH) droplet are studied. BAH droplet shows three-staged evaporation characteristics at high temperatures. Puffing and incomplete micro-explosion are observed during BAH droplet evaporation. Droplet lifetime of BAH is shorter than that of dodecane–hexadecane at high temperatures. Liquid-phase reaction of benzyl azides improves the evaporation of BAH droplets. Abstract: The evaporation characteristics of different dual component droplets are experimentally studied through a suspended droplet device and a high-speed video camera. The droplets of hexadecane, dodecane–hexadecane mixture and benzyl azides-hexadecane mixture are studied. The initial diameter of droplet is about 1.21–1.23 mm, and the elevated temperature environment in the range of 473 and 773 K is provided by an electric furnace. The results indicate that the evaporation trend of the dodecane–hexadecane blend droplet is the same as hexadecane at the different ambient temperatures, while the evaporation characteristics of the benzyl azides-hexadecane blend droplet are completely different from that of the dodecane–hexadecane at the high temperature of 673 K. The evaporation process of the benzyl azides-hexadecane blend droplet consists of three stages: transient heating, fluctuation evaporation and steady evaporation at the high ambient temperatures. The bubble formation and expansion, droplet distortion, puffing and incomplete micro-explosion are observed for benzyl azides-hexadecane droplet due to the reactivity of benzyl azides at liquid phase. Moreover, the reduction of the benzyl azides-hexadecane blend droplet lifetime is larger than that of the dodecane–hexadecane blend droplet with increasing ambient temperature. The increase of the liquid-phase reaction rate of benzyl azides is the main reason for improving the evaporation of the binary fuel droplet. In addition, with increasing benzyl azides mass fraction, the benzyl azides-hexadecane binary droplet lifetime decreases.